Three Books, One Message: Europe’s Forgotten Regions Can Be Innovative, Too - Hospers, Gert-Jan (European Spatial Research and Policy, 2025)
With a review of:Filipe TELES, Carlos RODRIGUES, Fernando RAMOS and Anabela BOTELHO (eds), Territorial Innovation in Less Developed Regions: Governance, Technologies, and Sustainability, Palgrave Macmillan, London/New York 2023, 305 pages, Matthias KIESE, Rasmus BECK, Dirk FORNAHL and Christian KETELS (eds), Beyond Innovation Hotspots: Clusters for Competitiveness and Transformation in Real Regions, Edward Elgar Publishing, Cheltenham 2024, 216 pages, and María del Carmen SÁNCHEZ CARREIRA, Paulo Jorge Reis MOURÃO and Bruno BLANCO-VARELA (eds), European Regional Policy and Development: Forgotten Regions and Spaces, Routledge, Abingdon 2024, 220 pages